Residential self-selection and travel : the relationship between travel-related attitudes, built environment characteristics and travel behaviour - Bohte, Wendy, 1977- (Sustainable urban areas, 2010)
Most Western national governments aim to influence individual travel patterns - at least to some degree - through the spatial planning of residential areas. Nevertheless, the extent to which the characteristics of the built environment influence travel behaviour remains the subject of debate among travel behaviour researchers. This work addresses the role of residential-self-selection, an important issue within this debate. Households may not only adjust their travel behaviour to the built environment where they live, but they may also choose a residential location that corresponds to their tr.